MtNPF6.5 mediates chloride uptake and nitrate preference in Medicago roots. (15th September 2021) - Xiao, Qiying; Chen, Yi; Liu, Cheng‐Wu; Robson, Fran; Roy, Sonali; Cheng, Xiaofei; Wen, Jiangqi; Mysore, Kirankumar; Miller, Anthony J; Murray, Jeremy D
Abstract: The preference for nitrate over chloride through regulation of transporters is a fundamental feature of plant ion homeostasis. We show that Medicago truncatula MtNPF6.5, an ortholog of Arabidopsis thaliana AtNPF6.3/NRT1.1, can mediate nitrate and chloride uptake in Xenopus oocytes but is chloride selective and that its close homologue, MtNPF6.7, can transport nitrate and chloride but is nitrate selective. The MtNPF6.5 mutant showed greatly reduced chloride content relative to wild type, and MtNPF6.5 expression was repressed by high chloride, indicating a primary role for MtNPF6.5 in root chloride uptake. MtNPF6.5 and MtNPF6.7 were repressed and induced by nitrate, respectively, and these responses required the transcription factor MtNLP1. Moreover, loss of MtNLP1 prevented the rapid switch from chloride to nitrate as the main anion in nitrate‐starved plants after nitrate provision, providing insight into the underlying mechanism for nitrate preference. Sequence analysis revealed three sub‐types of AtNPF6.3 orthologs based on their predicted substrate‐binding residues: A (chloride selective), B (nitrate selective), and C (legume specific). The absence of B‐type AtNPF6.3 homologues in early diverged plant lineages suggests that they evolved from a chloride‐selective MtNPF6.5‐like protein. Synopsis: Plants exhibit a pronounced preference for nitrate over chloride yet the mechanism behind this ion homeostasis remains poorly understood. This work reports a unique role for Medicago truncatula ion transporter MtNPF6.5 in chloride uptake and nitrate selectivity. Medicago truncatula encodes three orthologues of Arabidopsis thaliana AtNRT1.1/NPF6.3: MtNPF6.5, MtNPF6.6 and MtNPF6.7. MtNPF6.5 acts as a nitrate and chloride uptake carrier when expressed in Xenopus laevis oocytes, but is chloride selective. MtNPF6.5 is expressed in roots localizing to the plasma membrane. Loss of MtNPF6.5 reduces chloride content in plants devoid of nitrate. The transcription factor MtNLP1 is required for the suppression of MtNPF6.5 expression induced by nitrate uptake. Abstract : The identification of the chloride selective ion transporter MtNPF6.5 in Medicago truncatula roots illustrates how ion homeostasis between chloride and nitrate is maintained in the root.